Use of emergency departments by older people from residential care: A population based study - Ingarfield, S.; Finn, Judith; Jacobs, Ian; Gibson, N.; Holman, C.; Jelinek, G.; Flicker, L. (Oxford University Press, 2009)
Objective: to investigate the differences between emergency department (ED) presentations of older people who do and do not live in residential care facilities (RCFs). Design: a population-based retrospective cohort study. ED records linked to ambulance and hospital morbidity records. Setting: public EDs in Perth, Western Australia. Subjects: all patients 65 years and older who presented to EDs between 1 January 2003 and 31 December 2006 (n = 97,161). Measurements: patient demographic and clinical characteristics. Logistic regression was used to model the effect of living in RCFs on the likelihood of a particular ED diagnosis, hospital admission and in-hospital death. Results: the age-sex standardised rate of ED presentation for those living in RCFs was 1.69 times that of community dwellers. Compared to community dwellers, people from RCFs were older (mean age 84.7 years vs. 76.0 years, P < 0.001) and a lower proportion were male (28.7% vs. 46.7%, P < 0.001). Adjusting for age and sex revealed that people from RCFs were more likely to be diagnosed with pneumonia/influenza) odds ratio (OR) 1.94, 95% confidence interval (CI) = 1.72-2.19), urinary tract infections (OR 1.72, 95% CI 1.49%1.98) or hip fractures (OR 1.16, 95% CI 1.03-1.32); less likely to be diagnosed with circulatory system diseases (OR 0.69, 95% CI 0.64-0.75) or neoplasms (OR 0.47, 95% CI 0.31-0.72); more likely to be admitted (OR 1.13, 95% CI 1.06-1.20) and to die in hospital (OR 1.57, 95% CI 1.40-1.75). Conclusion: there are different patterns of ED presentations and hospital admissions of older people who do and do not live in RCFs. The appropriateness of these differences is uncertain.